Penerapan Algoritma Naïve Bayes untuk Analisis Sentimen Ulasan Produk E-Commerce - Nuari Anisa Sivi; Imam Mualim; Muhammad Taufik Kussofyan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
The rapid growth of e-commerce in Indonesia has generated a massive and continuous volume of product reviews. This user-generated content is vital for business intelligence, yet its sheer scale makes manual analysis inefficient, subjective, and practically impossible. Automated sentiment analysis is therefore crucial for businesses to efficiently understand customer feedback and market perception. This research addresses this gap by implementing the Naïve Bayes Classifier (NBC) algorithm to automatically classify the sentiment of Indonesian-language e-commerce product reviews. This study utilized a dataset of 2,000 reviews collected from a major e-commerce platform's